Enhanced subglacial discharge from Antarctica during meltwater pulse 1A - Tao Li; Laura F. Robinson; Graeme A. MacGilchrist; Tianyu Chen; Joseph A. Stewart; Andrea Burke; Maoyu Wang; Gaojun Li; Jun Chen; James W.B. Rae (Zenodo, 2023)
Compiled uranium series data of the deep-sea corals collected from Drake Passage.